INFLUENCE OF PLANT GROWTH REGULATORS ON ONTOGENESIS OF SPRING BARLEY VARIETIES - Gorobets, M. V.; Pysarenko, P. V.; Chaika, T. O.; Mishchenko, O. V.; Krykunova, V. Yu. (Scientific Progress & Innovations, 2021)
The aim of the study was to determine the influence of plant growth regulators on the productivity of spring barley in the production conditions of Poltava region. The evaluation of the effectiveness of using plant growth regulators and the natural mineral bischofite was conducted on the basis of experimental data. The experimental work was carried out in production conditions of “Gorobets S. G.” farm in Poltava region. Zircon and Epin-Extra growth regulators and 1 % solution of the natural mineral bischofite were used for crop treatment. Indicators of photosynthetic potential and net productivity of photosynthesis were deter-mined by the calculation method according to generally accepted techniques. As a result of five-year studies, the influence dynamics of plant growth regulators and bischofite natural mineral on net photosynthesis productivity, photosynthetic potential and leaf area duration were determined. It was found that for 3 years of experimental observations at treating with the above-mentioned growth regulators, stem elongation oc-curred 1–3 days earlier than in the control variant (without applying regulators). In 2017–2019, on the ex-perimental plot, plantlets of Helios variety were observed most rapidly after the treatment with Zircon stimu-lator, while in the control plantlets were observed 3 days later. Spring barley tillering of Helios variety and stem elongation was the fastest under the action of 1 % bischofite solution, and under the action of other stimulants (Epin-extra, Zircon) plantlets and full ripeness were recorded 3 days later. The application of Zircon stimulant and 1 % bischofite solution (for Helios and Parnassus varieties) accelerated the beginning of coming into ear phase by 2–4 days, while at using Epin-extra – only by 1–2 days. On the average, during the studies, the duration of development phases of spring barley plants, treated with stimulants, decreased by 1–4 days as compared with the control variant. When using growth regulators, the leaf area duration of spring barley crops increased in comparison with the control, which enables the most complete using of re-gional soil and climatic resources and get the maximum effect from the techniques of agro-technical effect. The proposed technological models allow reduce the duration of the growing season of spring barley crops without using desiccation. When treating crops with growth stimulants Epin-Extra, Zircon and 1 % bis-chofite solution in the tillering phase, the growing season is reduced by 2–4 days at cultivating spring barley on sod-podzolic soils; Epin-Extra stimulant and 1 % bischofite solution increase the assimilation leave sur-face of spring barley plants by 8.5 and 11.1 %, respectively, the potential of photosynthetic process – by 5.7 % and net photosynthesis productivity – by 3 and 10 %.